Dysphagia Caused by Spindle Cell Lipoma of Hypopharynx: Presentation of Clinical Case and Literature Review - Alberto Peña-Valenzuela; Nathalia García León (Case Reports in Otolaryngology)
Spindle cell lipoma of the hypopharynx is an extremely rare entity. Here, we present the first case of this lesion originated in the cricopharyngeal region, with symptoms of chronic progressive dysphagia, which can be confused with other pathologies; endoscopic and magnetic resonance imaging (MRI) evaluation are the methods of choice for its diagnostic approach. The best therapeutic approach is endoscopic resection with rapid recovery and few complications. Long-term followup is recommended, either endoscopic or imaging, given that it can be confused with an undiagnosed liposarcoma; additionally, its long-term behavior is unknown.